Kuliner sebagai Warisan Budaya : Eksplorasi Sate Kuok dan Makan Bedulang di Desa Pulau Belimbing - Hany Eliza; Elmustian Elmustian; Fatihah Fauziah; Ananda Nurrizka Efendi; Zaskia Putri Rhamadani Candra; Nirzara Utari; Salsabila Ahadani; Rahma Andini Gunawan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Indonesia has ethnoculinary diversity, one example of which is satay kuok and makan bedulang with the main side dishes being grilled fish kopiek dak betulang. This research aims to explore the role of traditional culinary delights, especially Sate Kuok and Makan Bedulang with the main side dish of grilled fish kopiek dak betulang, in strengthening the cultural identity of the Kampar community. Using participatory observation methods, this research analyzes the social and cultural values contained in these two dishes. The research results show that Sate Kuok not only functions as food, but also as a symbol of togetherness and social interaction in society. Order codes used in buying and selling transactions reflect local wisdom and strengthen relationships between community members. This research emphasizes the importance of preserving traditional culinary delights as part of cultural identity in the modern era. It is hoped that the results of this research can provide new insights into the relationship between culinary and cultural identity as well as contribute to the preservation of local cultural heritage.